2023
DOI: 10.1177/08982643231156286
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Minority Disparities in Subjective Cognitive Impairment: Do They Persist After Accounting for Psychological Distress?

Abstract: Objectives: Sexual minority older adults are a health disparate group with disproportionate rates of subjective cognitive impairment (SCI) and psychological distress. This study estimated risks of SCI by sexual orientation and gender, accounting for variations in psychological distress. Methods: We aggregated National Health Interview Survey data (2013–2018) of adults aged 45 and older and implemented logistic regressions of SCI indicators on sexual orientation and psychological distress, adjusting for covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…on both cognitive performance and brain metrics (e.g., volumes and functional connectivity) should be compared between SGM and non-SGM samples to clarify group-specific effects that could explain disparities. In fact, previous investigations found that depression was associated with worse cognitive performance equally in heterosexual and non-heterosexual older adults (Manca and Venneri, 2023) and that psychological distress did not explain higher rates of SCD in SGM people (Fredriksen-Goldsen et al, 2023). Future studies should also address the role of protective and resilience factors, either general (e.g., cognitive reserve (Stern et al, 2020)) or specific for SGM older adults (e.g., social support (Yang et al, 2024) and identity affirmation (Fredriksen-Goldsen et al, 2017)).…”
Section: Testing Hypothesis On Risk/protective Factorsmentioning
confidence: 95%
“…on both cognitive performance and brain metrics (e.g., volumes and functional connectivity) should be compared between SGM and non-SGM samples to clarify group-specific effects that could explain disparities. In fact, previous investigations found that depression was associated with worse cognitive performance equally in heterosexual and non-heterosexual older adults (Manca and Venneri, 2023) and that psychological distress did not explain higher rates of SCD in SGM people (Fredriksen-Goldsen et al, 2023). Future studies should also address the role of protective and resilience factors, either general (e.g., cognitive reserve (Stern et al, 2020)) or specific for SGM older adults (e.g., social support (Yang et al, 2024) and identity affirmation (Fredriksen-Goldsen et al, 2017)).…”
Section: Testing Hypothesis On Risk/protective Factorsmentioning
confidence: 95%